Monastic patronage in palaiologan constantinople - ERDOĞAN ULUHAN, ESRA GÜZEL (Andys's Publishers, 2022)
This present study investigates the general characteristics of monastic patronage in Constantinople during the Palaiologan period (1261-1453). It focuses on the groups that were interested in patronage; namely the aristocracy, ruling family and ecclesiastical hierarchy.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)